Competitiveness of the dairy goat industry in Malaysia: management view - Yusoff, Melissa Alina; Mohd Nawi, Nolila; Ismail, Mohd Mansor; Abdullah, Amin Mahir; Man, Norsida (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Dairy goat industry is a small entity in the Malaysian livestock sector and one of the important components of the agricultural sector. The government has taken various researches in attempt to increase the level of goat's milk production to ensure the sustainability of the industry. However, issues pertaining to slow progress of goat milk industry and low investment from the public on the goat milk production are due to limited knowledge in the competitiveness of the industry. Dairy goat farmers are still facing the problem of low milk production which has recognized as the main challenge to the industry. Research on competitiveness of goat milk provides important avenue to attract future investments and appropriate policy development for the industry. Hence, the study was aimed to analyze the competitiveness of Malaysian dairy goat industry. A series of focus group discussions with supply chain players and policy makers were undertaken to determine the competitiveness of the industry. In summary, the findings of this research suggest that the competitiveness of the dairy goat industry follows the Diamond Porter Model.